Curcumin, a Multifaceted Hormetic Agent, Mediates an Intricate Crosstalk between Mitochondrial Turnover, Autophagy, and Apoptosis. (20th July 2020) - Rainey, Nathan Earl; Moustapha, Aoula; Petit, Patrice Xavier
Abstract : Curcumin has extensive therapeutic potential because of its antioxidant, anti-inflammatory, and antiproliferative properties. Multiple preclinical studies in vitro and in vivo have proven curcumin to be effective against various cancers. These potent effects are driven by curcumin's ability to induce G2/M cell cycle arrest, induce autophagy, activate apoptosis, disrupt molecular signaling, inhibit invasion and metastasis, and increase the efficacy of current chemotherapeutics. Here, we focus on the hormetic behavior of curcumin. Frequently, low doses of natural chemical products activate an adaptive stress response, whereas high doses activate acute responses like autophagy and cell death. This phenomenon is often referred to as hormesis. Curcumin causes cell death and primarily initiates an autophagic step (mitophagy). At higher doses, cells undergo mitochondrial destabilization due to calcium release from the endoplasmic reticulum, and die. Herein, we address the complex crosstalk that involves mitochondrial biogenesis, mitochondrial destabilization accompanied by mitophagy, and cell death.